Case study of Lithuanian strategic company’s “Mažeikiųnafta” privatization - Manuela Tvaronavičienė; Kristina Kalašinskaitė; Kęstutis Peleckis (Business: Theory and Practice, 2008)
The paper aims at presenting a case study, in which foreign direct investment does not provided expected in-novative spillovers in technology, management or marketing fields. Efficiency of state policy in that particular case has been questioned; actual stimuli of a foreign investor discussed. it is assumed that analysis of that particular case study of globalization process of Lithuanian strategic oil refinery would provide us with additional evidences leading to formulation of new insights into driving forces of foreign direct investment, especially channeling through privatization.